Quantum aspects of non-invertible flavor symmetries in intersecting/magnetized D-brane models - Shuta Funakoshi; Tatsuo Kobayashi; Hajime Otsuka (Journal of High Energy Physics)
Abstract We discuss selection rules of chiral matters in type IIA intersecting and IIB magnetized D-brane models on toroidal orbifolds. Since the chiral matters on toroidal orbifolds are labeled by a certain conjugacy class of the gauged orbifold group, the selection rules involve non-trivial fusion rules. We find that the representation of the chiral matters is described by a D 4 flavor symmetry for an even number of magnetic fluxes or winding numbers at tree level. Furthermore, the D 4 symmetry still remains even when we take into account loop effects. We also study non-perturbative effects such as D-brane instantons.